Structural and optical properties of individual Zn2GeO4 particles embedded in ZnO. (19th March 2019) - Granerød, Cecilie S; Aarseth, Bjørn L; Nguyen, Phuong Dan; Bazioti, Calliope; Azarov, Alexander; Svensson, Bengt G; Vines, Lasse; Prytz, Øystein
Abstract: Functionalizing transparent conducting oxides (TCOs) is an intriguing approach to expand the tunability and operation of optoelectronic devices. For example, forming nanoparticles that act as quantum wells or barriers in zinc oxide (ZnO), one of the main TCOs today, may expand its optical and electronic tunability. In this work, 800 keV Ge ions have been implanted at a dose of 1 × 10 16 cm −2 into crystalline ZnO. After annealing at 1000 °C embedded disk-shaped particles with diameters up to 100 nm are formed. Scanning transmission electron microscopy shows that these are particles of the trigonal Zn2 GeO4 phase. The particles are terminated by atomically sharp facets of the type 11 2 ̄ 0, and the interface between the matrix and particles is decorated with misfit dislocations in order to accommodate the lattice mismatch between the two crystals. Electron energy loss spectroscopy has been employed to measure the band gap of individual nanoparticles, showing an onset of band-to-band transitions at 5.03 ± 0.02 eV. This work illustrates the advantages of using STEM characterization methods, where information of structure, growth, and properties can be directly obtained.